2021
DOI: 10.3389/fpsyg.2021.752793
|View full text |Cite
|
Sign up to set email alerts
|

How Technology Tools Impact Writing Performance, Lexical Complexity, and Perceived Self-Regulated Learning Strategies in EFL Academic Writing: A Comparative Study

Abstract: Students experience different levels of autonomy based on the mediation of self-regulated learning (SRL), but little is known about the effects of different mediation technologies on students' perceived SRL strategies. This mixed explanatory study compared two technology mediation models, Icourse (a learning management system) and Icourse+Pigai (an automatic writing evaluation system), with a control group that did not use technology. A quasi-experimental design was used, which involved a pre and post-interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…They rated AWE as easy to use, fair, and useful but critiqued the tool in terms of the quantity, specificity, and personalization of the feedback (Roscoe et al, 2017). Teachers were generally positive about the system's utility but still pointed out limitations such as the confusion of some AWE feedback and the inconvenience of incorporating teacher feedback into the system (Han et al, 2021).…”
Section: Application Of Awe In Writing Learningmentioning
confidence: 99%
“…They rated AWE as easy to use, fair, and useful but critiqued the tool in terms of the quantity, specificity, and personalization of the feedback (Roscoe et al, 2017). Teachers were generally positive about the system's utility but still pointed out limitations such as the confusion of some AWE feedback and the inconvenience of incorporating teacher feedback into the system (Han et al, 2021).…”
Section: Application Of Awe In Writing Learningmentioning
confidence: 99%
“…In the context of this study, lexical complexity is adopted as an indicator of EFL learners' vocabulary learning performance. In literature, a considerable number of EFL studies have investigated the role of lexical complexity in language learning, but most of their data were written English (e.g., Barrot and Gabinete, 2021;Han et al, 2021). In contrast, few studies have investigated oral lexical complexity in the context of EFL learning (Bulté and Roothooft, 2020).…”
Section: The Triadic Componential Caf Frameworkmentioning
confidence: 99%
“…In response, the present study seeks to address this gap by examining EFL learners' lexical complexity in their oral English. Although lexical complexity can be investigated through various aspects such as diversity, density and sophistication (Skehan, 2003;Bulté and Housen, 2012), complexity is primarily shaped by lexical diversity, and operationally, lexical diversity is usually the most frequently used measure for assessing lexical complexity (e.g., Ågren et al, 2012;Han et al, 2021) and lexical development (e.g., Crossley et al, 2009). In the current study, therefore, as has been the case for most studies so far, complexity is quantified using lexical diversity in the tripartite CAF framework.…”
Section: The Triadic Componential Caf Frameworkmentioning
confidence: 99%
“…This review of the small body of literature combining SRL and MW shows the mixture of correlational studies that examined relations between SRL and writing performance/quality (Farsani et al, 2014;Zhang, 2016, 2018;Han et al, 2021), four intervention studies reporting on students' writing quality and some SRL skills (Fathi and Feizollahi, 2020;Teng and Zhang, 2020;Altas and Mede, 2021;Chen et al, 2021), or proposed untested SRL writing programs/instructional practices (Oxford, 2011;Andrade and Evans, 2013). While these lines of research contribute to our understanding of how SRL associates with MW and four intervention studies provide initial evidence of improvement in MW and SRL skills, they do not provide conclusive results on how SRL writing instructional methods work in authentic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has shown that SRL is associated with improved performance by native speakers of English across disciplines and age-groups (Graham, 2006;De Corte et al, 2011;Kitsantas and Kavussanu, 2011;Tonks and Taboada, 2011), research on the usefulness of SRL instruction in developing scholarly writing skills in college students, especially ELs, is scarce and under-developed. A small number of scholars have recognized the importance of SRL in developing writing skills of ELs (Oxford, 2011;Andrade and Evans, 2013;Teng and Zhang, 2016, 2018Fathi and Feizollahi, 2020;Altas and Mede, 2021;Han et al, 2021). Research shows that the SRL processes that occur during writing by ELs are similar to those of native speakers.…”
Section: Introductionmentioning
confidence: 99%